THE RELATIONSHIP BETWEEN PERCEIVED SERVICE QUALITY AND THE TRUST OF PATIENTS WITH DIABETES MELLITUS AT THE KARTASURA HEALTH CENTER - Hidayati, Nurul; Umaroh, Ayu Khoirotul (HEARTY, 2025)
One of the chronic diseases whose incidence rate continues to increase, especially in Sukoharjo Regency, which shows a high number of cases at the Kartasura Health Center is Diabetes Mellitus (DM). This disease requires optimal attention and long-term treatment, where the quality of health services plays an important role in its success. This study was conducted to analyze the relationship between service quality and the trust of patients with diabetes mellitus at the Kartasura Health Center. The method applied in this study was a quantitative approach with a cross-sectional study design, using a total sampling technique, where data were collected through questionnaires distributed to 50 diabetes mellitus prolanis patients who attended the Puskesmas in three consecutive months. The results of the analysis showed a significant positive relationship between service quality and patient trust with a moderate level of relationship strength (p-value0.044; r=0.287), indicating that the better the quality of services provided, the higher the level of patient trust in the health facility. This study confirms the importance of improving the quality of health center services to build patient trust which in turn can support patient adherence to recommended care and treatment.